Nonresonant leptoquark with multigeneration couplings for μμjj and μνjj at the LHC - Alvarez, Ezequiel (2019)
CMS has recently reported [A. M. Sirunyan (CMS Collaboration), Search for pair production of second-generation leptoquarks at s=13 TeV, Phys. Rev. D 99, 032014 (2019).] a moderate excess in the μνjj final state in a second-generation leptoquark search, but they have disregarded it because the excess is not present in the μμjj final state and because they do not observe the expected resonant peak in the distributions. As a proof of concept, we show that a simple leptoquark model including second- and third-generation couplings with non-negligible single- and nonresonant production in addition to usual pair production could explain the data - excess (μνjj), lack of excess (μμjj), and missing peak in the distributions - while being in agreement with collider constraints. We take this result and analysis as a starting point of a reconsideration of the ATLAS and CMS second-generation leptoquark searches. We also discuss which consequences and modifications should be performed in the searches to test if this deviation would correspond to a new physics signal. We observe that low-energy flavor constraints can be avoided by adding heavier particles to the model.